The Effect of Workplace Spirituality on Organizational Citizenship Behavior of BUMD Employees: Mediating Organizational Commitment - Octavianum, Mazura; Fitria, Yuki (Universitas Negeri Padang, 2025)
Using the Structural Equation Modeling (SEM) approach, this study seeks to ascertain how organizational citizenship behavior is impacted by workplace spirituality among Perumda Air Minum Tirta Sago Payakumbuh City employees, as well as the mediating function of organizational commitment. Permanent employees of Perumda Air Minum Tirta Sago Payakumbuh City make up the research population in this quantitative, explanatory study. Total sampling is the sampling technique employed, meaning that 67 permanent employees make up the study's sample size. A Likert scale questionnaire was used to gather data, and the findings indicated that workplace spirituality had a positive and significant impact on organizational citizenship behavior. Additionally, it was discovered that the association between workplace spirituality and organizational citizenship behavior was significantly mediated by organizational commitment. These results advance our knowledge of the significance of organizational commitment and workplace spirituality in enhancing organizational citizenship behavior among Perumda Air Minum Tirta Sago Payakumbuh City employees.